Pengembangan Pemikiran Pendidikan Islam Nusantara Berbasis Kearifan Lokal dan Nilai Rahmatan lil ‘Alamin - Moh. Hazim Ahrori; Mariana (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study aims to analyze and develop a framework for Islamic education in the Indonesian archipelago based on local wisdom and rahmatan lil 'alamin values, focusing on how the integration of these two aspects can strengthen the curriculum, methodology, and character building of students. The method used is library research with a qualitative-descriptive approach, where data is collected through the study of documents, books, scientific articles, and secondary literature related to Islamic education, local wisdom, and the principles of rahmatan lil 'alamin. The results of the study indicate that the integration of local wisdom strengthens moderate social and cultural values, the application of the principles of rahmatan lil 'alamin fosters an inclusive attitude and social responsibility, and the synergy of both in the curriculum and educational methodology produces a contextual, humanistic model of Islamic education in the Indonesian archipelago that is able to face contemporary challenges effectively.